Extreme Diversity of IgGs Against Histones, DNA, and Myelin Basic Protein in the Cerebrospinal Fluid and Blood of Patients with Multiple Sclerosis - Kostrikina, Irina A. (Biomolecules, 2020)
It was recently shown that IgGs from sera of multiple sclerosis (MS) patients are active in the hydrolysis of DNA and myelin basic protein (MBP). We first analyzed the relative concentration of antibodies against five histones (H1, H2a, H2b, H3, and H4) in the cerebrospinal fluid (CSF) and serum of patients with MS. The relative concentrations of blood and CSF IgGs against histones and their activity in the hydrolysis of five histones varied greatly from patient to patient. However, all 28 IgG preparations were hydrolyzed from one to five histones. Relative activities and correlation coefficients among the activities of IgGs from serum and CSF in the hydrolysis of five histones (H1, H2a, H2b, H3, and H4), DNA, and MBP were calculated. It was shown that auto-IgGs from CSF and sera of MS patients are extremely heterogeneous in their affinity to histones, MBP, and DNA. The heterogeneity of IgG-abzymes hydrolyzing DNA, MBP, and histones from CSF and sera was also demonstrated using their isoelectrofocusing. The isofocusing profiles DNase, MBP-, and histone-hydrolyzing activities of IgGs may be very different for various individuals, but the total IgG subfractions with all their activities are distributed from pH 3 to 10.